Emergence of a Hypervirulent Tigecycline-Resistant Klebsiella pneumoniae Strain Co-producing blaNDM–1 and blaKPC–2 With an Uncommon Sequence Type ST464 in Southwestern China - Hao, Jingchen; Zhang, Bangqin; Deng, Jiamin; Wei, Yueshuai; Xiao, Xue; Liu, Jinbo (Frontiers in Microbiology, 2022)
Emergence of blaNDM-1 and blaKPC-2 co-producing Klebsiella pneumoniae strains is currently attracting widespread attention, but little information is available about their tigecycline resistance, virulence, and prevalence in Southwest China. In July 2021, an extensively drug-resistant K. pneumoniae strain AHSWKP25 whose genome contained both blaNDM-1 and blaKPC-2 genes was isolated from the blood of a patient with the malignant hematological disease in Luzhou, China. We investigated the resistance profiles of AHSWKP25 using microbroth dilution, agar dilution, modified carbapenemase inactivation (mCIM), and EDTA-modified carbapenemase inactivation methods (eCIM). The virulence of AHSWKP25 was assessed through string tests, serum killing assays, and a Galleria mellonella larval infection model. Conjugation and plasmid stability experiments were conducted to determine the horizontal transfer capacity of plasmids. And efflux pump phenotype test and real-time quantitative reverse transcription-PCR (RT-PCR) were used to determine its efflux pump activity. Sequencing of AHSWKP25 determined that AHSWKP25 belonged to ST464, which is resistant to antibiotics such as carbapenems, tetracyclines, fluoroquinolones, tigecycline, and fosfomycin. The efflux pump phenotype tests and RT-PCR results demonstrated that efflux pumps were overexpressed in the AHSWKP25, which promoted the tigecycline resistance of the bacteria. AHSWKP25 also showed hypervirulence and serum resistance in vitro model. AHSWKP25 carried several different plasmids that contained blaNDM-1, blaKPC-2, and mutated tet(A) genes. Sequence alignment revealed that the plasmids carrying blaNDM-1 and blaKPC-2 underwent recombination and insertion events respectively. We demonstrated that an X3 plasmid carrying blaNDM-1 was transferred from pSW25NDM1 to E. coli J53. We also identified missense mutations in the ramR, rcsA, lon, and csrD genes of AHSWKP25. Our results highlighted the potential of blaNDM-1 and blaKPC-2 co-producing K. pneumoniae strains to further develop antimicrobial resistance and hypervirulent phenotypes, but measures should be taken to closely monitor and control the spread of superbugs with multidrug-resistant phenotypes and hypervirulence.